1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1719::aid-immu1719>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

TCRζ is transported to and retained in the Golgi apparatus independently of other TCR chains: implications for TCR assembly

Abstract: It is generally assumed that TCR assembly occurs in the endoplasmic reticulum (ER), and ER retention/degradation signals have been identified in several of the TCR chains. These signals are probably responsible for retention of incompletely assembled TCR complexes and free TCR chains in the ER. This study focused on the intracellular localization and transport of partially assembled TCR complexes as determined by confocal microscopy analyses. We found that none of the TCR chains except for TCR´were allowed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
(15 reference statements)
3
28
0
1
Order By: Relevance
“…Perinuclear anti-CD3ε staining is something we have observed earlier6 and Jurkat T cells with undetectable CD3 surface expression have recently been reported34. Moreover, both TCRα and CD3ε have been reported to localise to the perinuclear membrane in addition to intracellular vesicles and the cell surface4647 even if none of these studies used synchronised cells. Together the data suggest that not only CD3ε, but the entire TCR-CD3 complex, relocates to the perinuclear membrane during cell cycle progression to the S-phase and that signalling predominantly occurs during the G1-phase.…”
Section: Discussionmentioning
confidence: 50%
“…Perinuclear anti-CD3ε staining is something we have observed earlier6 and Jurkat T cells with undetectable CD3 surface expression have recently been reported34. Moreover, both TCRα and CD3ε have been reported to localise to the perinuclear membrane in addition to intracellular vesicles and the cell surface4647 even if none of these studies used synchronised cells. Together the data suggest that not only CD3ε, but the entire TCR-CD3 complex, relocates to the perinuclear membrane during cell cycle progression to the S-phase and that signalling predominantly occurs during the G1-phase.…”
Section: Discussionmentioning
confidence: 50%
“…The experiments presented here clearly demonstrate that all assembly steps can occur within the ER. However, recent work from Geisler and co-workers (Dietrich et al, 1999) has shown that in Jurkat T-cell mutants lacking various TCR-CD3 Figure 5 Stoichiometry of a TCR-CD3 assembly intermediate lacking the z chain. Assembly reactions were carried out as in previous experiments using mRNAs encoding all subunits with the exception of the z chain.…”
Section: Stoichiometry Of Key Assembly Intermediatesmentioning
confidence: 99%
“…Golgi apparatus restriction is not uncommon. The TCR is retained in the Golgi until oligomerization is completed [56], viral proteins are retained in the Golgi apparatus [57], and a variety of glycosyltransferases resides in the Golgi apparatus [58]. ␤1-integrins have been shown to be confined to the ER/Golgi apparatus prior to surface expression [51].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of heterodimerization relieving Golgi apparatus retention also exist in the literature. Efficient TCR cell-surface expression requires complete assembly of TCR components [64], as the TCR homodimer is retained in the Golgi apparatus until it associates with the assembled CD3␥ variable receptor heterodimer-CD3␦ complex, resulting in release of TCR Golgi apparatus retention and subsequent relocalization to the cell surface [56]. Thus, CD11d and CD18 surface expression falls into a generally recognized mechanism of retaining individual subunits intracellularly until a functional protein can be trafficked to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation